KRONİK KARACİĞER HASTALARINDA HEPATİT A AŞISI YAPILMALI MI ? - ERKAN, Tülin; ÇULLU, Figen; KUTLU, Tufan; ÇERÇİÖZKAN, Hilda; KIRAY, Evrim (Cerrahpaşa Medical Journal, 2019)
Background and design.- Hepatitis A virus (HAV) infection which commonly is seen in childhood in developing countries and may be responsible for fulminant hepatic failure. In this study, antibody to HAV in the patients with chronic liver disease was studied retrospectively. Vaccination of these patients who are under risk is recommended. Results.- Fifty-eight of 171 patients had had anti HAV IgG (+) and 113 of 171 had anti HAV IgG(-). Acute HAV infection was occurred in 7 patients during follow-up. The mean age of the anti HAV IgG (+) and (-) groups was 9.9± 4.6 and 8.7± 4.3 years respectively. Conclusion.- Although in our country, the prevalence of exposure to HAV changes with age and regions (54.5% at 3-10 years), there is a decrease in the ratio with improvement of hygienic conditions. Because the possibility of HAV infection in patients with chronic liver disease during adolescent or elderly is more dangerous, passive immunization of these patients is recommended.